Reducing oral corticosteroids in severe asthma (ROSA Project): a nationwide Portuguese consensus - Loureiro, Cláudia Chaves (2021)
Introduction and objectives: We aimed to build a national consensus to optimize the use of oral corticosteroids (OCS) in severe asthma in Portugal. Material and methods: A modified 3-round Delphi including 65 statements (topics on chronic systemic corticotherapy, therapeutic schemes, asthma safety and monitoring) was performed via online platform (October-November 2019). A five-point Likert-type scale was used (1- ‘strongly disagree’; 5-‘strongly agree’). Consensus threshold was established as a percentage of agreement among participants ≥90% in the 1st round and ≥85% in the 2nd and 3rd rounds. The level of consensus achieved by the panel was discussed with the participants (face-to-face meeting). Results: Forty-eight expert physicians in severe asthma (specialists in allergology and pulmonology) participated in the study. Almost half of the statements (28/65; 43.1%) obtained positive consensus by the end of round one. By the end of the exercise, 12 (18.5%) statements did not achieve consensus. Overall, 87% of physicians agree that further actions for OCS cumu-lative risk assessment in acute asthma exacerbations are needed. The vast majority (91.7%)demonstrated a favorable perception for using biological agents whenever patients are eligible.Most participants (95.8%) are more willing to accept some degree of lung function deteriorationcompared to other outcomes (worsening of symptoms, quality of life) when reducing OCS dose.Monitoring patients’ comorbidities was rated as imperative by all experts.Conclusions: : These results can guide an update on asthma management in Portugal and shouldbe supplemented by studies on therapy access, patients’ adherence, and costs.